Pathologic spinopelvic balance in patients with hip osteoarthritis: preoperative screening and therapeutic implications = Pathologische spinopelvine Balance bei Patientenmit Coxarthrose : präoperatives Screening und therapeutische Konsequenzen - Innmann, Moritz Maximilian; Weishorn, Johannes; Beaulé, Paul E.; Grammatopoulos, George; Merle, Christian (Der Orthopäde, 2020)
Recently spinopelvic balance and mobility, i.e. the dynamic interaction of the spine, pelvis and the femur in the sagittal plane between different postures, has been identified as a relevant factor influencing the outcome of primary total hip arthroplasty (THA). Individual spinopelvic balance and mobility seem to affect patient reported outcome and the risk of impingement and dislocation following THA. The aim of this article is to provide a concise overview of normal and pathologic spinopelvic alignment, to characterize relevant spinopelvic parameters and the diagnostic assessment in patients with hip OA and to discuss potential implications for THA with respect to implant selection and component orientation.
Gesehen am 25.09.2025